Hubungan Kemampuan Komunikasi Matematis Dengan Self Confidence Pada Pembelajaran Matematika Kelas V SDN Banyu Ajuh 06 - Izzah Lintang Masyithoh; Rika Wulandari (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
The purpose of this study was to determine the relationship between mathematical communication skills and self-confidence in mathematics learning for fifth grade students at SDN Banyu Ajuh 06, Kamal, Banyu Ajuh, Kec. Kamal, Kab. Bangkalan on building materials. This research uses quantitative methods. The research population is all fifth grade students for the 2022/2023 Academic Year. Sampling in this study using a total sample. The research sample was 22 students. Data was collected using test questions and observation sheets. The results of the study show that 1) there is a positive relationship between mathematical communication ability and self-confidence with a moderate level of relationship, 2) that the relationship between mathematical communication ability and self-confidence is 29.4%, while 70.6% is influenced by other variables .